A dark inheritance / 1 - D'Lacey, Chris (D'Lacey, Chris. UNICORNE files, 2014)
When Michael Malone saves a dog, he discovers that he has paranormal abilities, which bring him to the attention of a secret organization, UNICORNE, but he plans to use the ability to find out what happened to his father, who mysteriously vanished three years earlier, and save his new friend, Freya.